Caracterização mecânica e microestrutural do aço MARAGING 300, soldado a plasma e submetidas a reparos - Silva, Deivid Ferreira da [UNESP] (2014)
This study aims to evaluate and quantify the possible losses of mechanical resistance in the welded join of MARAGING 300 steel submitted within three after repairs in the cords of the welded. The Institute of Aeronautics and Space (IAE) designs, develops and manufactures sounding rockets and satellite launcher vehicles (VLS) using solid propellant and the motor case is responsible for supporting the pressure during the burning of this propellant. Currently, the motor case is made of 300M-ESR steel. Due to a number of advantages found in the mechanical properties and the manufacturing process, IAE is studying the replacement of 300M-ESR steel by MARAGING 300 steel. The welding method used for achievement of the work was the process of plasma arc welding (paw) in a single pass, using the keyhole technique with filler metal. The welded joints are evaluated by adopting non-destructive testing acceptance criteria according to AWS D17.1. In this work, the repairs were done, manually, using the tungsten inert gas method (TIG). Measures of mechanical strength, Vickers hardness (HV), chemical analysis, metallographic analysis and fractography of the welded joint were made at the various welding conditions. The results show that after welding and repair and before the aging heat treatment the adjacent region to the weld fusion zone have hardness lower than other regions affected thermally. It is due to segregation of solute in the region. After aging treatment there is an increase in levels of hardness of about 200HV, but the fusion zone and near the weld zone with hardness remain slightly lower than the rest of the material. The analyzes of the fractured surface showed that the rupture of the specimens occurred in the region of the heat affected zone near the weld , and has a appearance of mixed fractures with formation predominantly of microvoid (dimples) ... (Complete abstract click electronic access below)